An insight on the impact of teleost whole genome duplication on the regulation of the molecular networks controlling skeletal muscle growth - Duran, Bruno Oliveira Silva [UNESP]; de la Serrana, Daniel Garcia; Zanella, Bruna Tereza Thomazini [UNESP]; Perez, Erika Stefani [UNESP]; Mareco, Edson Assunção; Santos, Vander Bruno; Carvalho, Robson Francisco [UNESP]; Dal-Pai-Silva, Maeli [UNESP] (Public Library of Science (PLoS), 2021)
Fish muscle growth is a complex process regulated by multiple pathways, resulting on the net accumulation of proteins and the activation of myogenic progenitor cells. Around 350–320 million years ago, teleost fish went through a specific whole genome duplication (WGD) that expanded the existent gene repertoire. Duplicated genes can be retained by different molecular mechanisms such as subfunctionalization, neofunctionalization or redundancy, each one with different functional implications. While the great majority of ohnolog genes have been identified in the teleost genomes, the effect of gene duplication in the fish physiology is still not well characterized. In the present study we studied the effect of WGD on the transcription of the duplicated components controlling muscle growth. We compared the expression of lineage-specific ohnologs related to myogenesis and protein balance in the fast-skeletal muscle of pacus (Piaractus mesopotamicus—Ostariophysi) and Nile tilapias (Oreochromis niloticus—Acanthopterygii) fasted for 4 days and refed for 3 days. We studied the expression of 20 ohnologs and found that in the great majority of cases, duplicated genes had similar expression profiles in response to fasting and refeeding, indicating that their functions during growth have been conserved during the period after the WGD. Our results suggest that redundancy might play a more important role in the retention of ohnologs of regulatory pathways than initially thought. Also, comparison to non-duplicated orthologs showed that it might not be uncommon for the duplicated genes to gain or loss new regulatory elements simultaneously. Overall, several of duplicated ohnologs have similar transcription profiles in response to pro-growth signals suggesting that evolution tends to conserve ohnolog regulation during muscle development and that in the majority of ohnologs related to muscle growth their functions might be very similar.